Topological triviality of families of real isolated singularities and their Milnor fibrations - Santos, Raimundo Nonato Araújo Dos (MATHEMATICA SCANDINAVICA, 2005)
The aim of this paper is to study the topological triviality and the topological equivalence of the Milnor fibrations for families of real analytic map germs with no coalescing of critical points.